2019
DOI: 10.1108/ecam-10-2018-0429
|View full text |Cite
|
Sign up to set email alerts
|

Building information modelling (BIM) and the CDM regulations interoperability framework

Abstract: Purpose Building information modelling (BIM) has received wide coverage within the research, academic and industry communities over the last decade. Yet, its degree of integration with various industry standards in the architecture, engineering and construction sector varies extensively. An exploratory research approach explores the interoperability between the construction design and management (CDM) regulations and BIM. The paper aims to discuss this issue. Design/methodology/approach The research design c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…For instance, the use of BIM could also provide checking for compliance with specific safety requirements, thus allowing for better decision of the design, which results in enhanced construction site safety (Melzner et al, 2013), as well as the aspect of sustainability of a project (Dewlaney and Hallowell, 2012). It is worth highlighting that even though these tools could facilitate PtD implementation, the study by Mzyece et al (2019) indicated that having BIM could only fulfil between 4 (18%) to 9 (41%) roles and responsibilities of designer and principal designer respectively, as stipulated in the CDM regulations.…”
Section: Technical Skillsmentioning
confidence: 99%
“…For instance, the use of BIM could also provide checking for compliance with specific safety requirements, thus allowing for better decision of the design, which results in enhanced construction site safety (Melzner et al, 2013), as well as the aspect of sustainability of a project (Dewlaney and Hallowell, 2012). It is worth highlighting that even though these tools could facilitate PtD implementation, the study by Mzyece et al (2019) indicated that having BIM could only fulfil between 4 (18%) to 9 (41%) roles and responsibilities of designer and principal designer respectively, as stipulated in the CDM regulations.…”
Section: Technical Skillsmentioning
confidence: 99%
“…Although the construction industry had a slow adoption of new and advanced technologies (Mzyece et al , 2019), technology and innovations were expected to improve both the quality of the construction sectors (Maskuriy et al , 2019). New tools such as three-dimensional (3D) imaging (Wei et al , 2019), 3D printing (Tay et al , 2017), four-dimensional (4D) simulation (Kunieda et al , 2019), building information modeling (BIM) (Mzyece et al , 2019), drones, virtual reality and augmented reality were all potential and applied for CDWM practices. These high technologies enabled the project stakeholders to simulate the generation of CDW, resulting in proper understanding and minimizing CDW.…”
Section: Discussionmentioning
confidence: 99%
“…Among high technology applications, BIM is a prominent approach for minimizing construction waste generation (Mzyece et al , 2019; Chiu and Lai, 2020). The nation-wide BIM implementation in Vietnam will begin in 2021 supported by the strong foundation of legal frameworks (Bui, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of skilled technical expertise not only puts the digital data at risk but also hinders BIM from providing optimum benefits to its users. Plenty of studies reported the issue of software interoperability that stems from the use of various software that comes with different formats that are incompatible with each other, thus causing difficulties during the process of exchanging data among the team members (Philp & Frise, 2014;Mzyece, Ndekugri, & Ankrah, 2019;Costa & Sicilia, 2020;Utkucu & Sözer, 2020). This issue is severe particularly when a single integrated model working environment is involved, which is from BIM Level 2 and above when high level of interoperability is required during the data exchange process.…”
Section: Technical Issuesmentioning
confidence: 99%